Main Characteristics of Lower Gastrointestinal Bleeding in Patients Treated at a Reference Hospital - Alvaro Gastaldi Nantes; Glenda Maria Abreu; Guilherme Henrique Pereira de Ávila Borges; Isabela Cruz Momm; Karina de Araujo Mazzini; Luiz Gabriel Lani; Raphael Londero de Araujo; Carlos Henrique Marques dos Santos (Journal of Coloproctology)
Lower gastrointestinal bleeding (LGB) originates below the angle of Treitz and can result from vascular, inflammatory, neoplastic, or traumatic causes. This study analyzed the clinical and epidemiological profiles of LGB patients treated at Hospital Regional do Mato Grosso do Sul from 2017 to 2022, exploring the relationship between LGB etiology and colonoscopy performance. A retrospective analysis of 303 patients examined variables such as year of service, management approach, hospital stay, Oakland score, age, sex, and race. Most patients were hospitalized between 2018 and 2019, with hospitalization being the primary management strategy. The majority were male (59.4%), over 60 years old (55.1%), and mixed race (53.5%). The mean length of hospital stay was 10.6 days, and the average Oakland score was 20.28. Clinical findings showed 64.7% had no prior LGB history, with an average systolic blood pressure of 91.24 mmHg and a heart rate of 129.61 bpm. Colonoscopy revealed diverticular disease as the most common finding (39.6%), and the most frequent bleeding types were enterorrhagia (47.5%) and melena (37.0%). Significant associations were found between bleeding type, hemoglobin levels, and outcomes, with melena linked to lower hemoglobin levels and higher mortality. Colonoscopy results were also associated with outcomes, showing higher mortality in colitis patients. These findings emphasize the impact of clinical and demographic factors in LGB management and suggest further research into targeted interventions.